BIOM-09. MULTIPLEX ANALYSIS OF CSF EXTRACELLULAR VESICLES OF INTRASPINAL TUMORS. (9th November 2020) - Ricklefs, Franz; Stevic, Ines; Mende, Christian; Welsh, Joshua; Jones, Jennifer; Westphal, Manfred; Lamszus, Katrin; Eicker, Sven
Abstract: BACKGROUND: Extracellular vesicles (EVs) play an important role in cell-cell communication in different types of tumors, carrying multiple layers of biological functional molecules, including proteins, RNA, DNA and lipids. We previously demonstrated that extracellular vesicles (EV) from central nervous system tumors reflect the molecular subtype of the original tumor and mediate an exchange of pro-oncogenic signals. Their implication as biomarkers in tumor disease is under current investigation. It is unclear, however, to what extent cerebrospinal fluid (CSF) EVs from intraspinal tumors are utilizable for diagnostical purposes and how their marker profiles overlap with EVs derived from non tumorous EVs. We analyzed CSF EVs of intraspinal tumors to define CSF EV profiles that allow tumor subtype classification. METHODS: EVs were isolated from CSF of patients suffering from intraspinal meningioma (n=5), ependymoma (n=7) and neurinoma (n=5). Patients suffering from normal pressure hydrocephalus were used as controls (n=5). EVs were analyzed by multiplex bead based assay, immunoblotting, electron microscopy and NTA. RESULTS: CSF EVs were 97.21 ± 3.37nm (intraspinal tumor patients) and 101.6 ± 3.68nm (controls) in sizes and showed vesicular structures by electron microscopy. Particle number were not significantly different between both groups (p = 0.103). Using our 37 protein mutliplex EV profiling kit we found 29 proteins to be expressed in a sufficient manner on CSF EVs. CSF EVs of intraspinal meningioma showed elevated CD62P, HLA-DR, CD40, CD42a and CD45 expression levels, while ependymoma showed decreased levels of CD9, CD63, CD81, whereas neurinomas had elevated levels of SSEA-3 and CD25. CONCLUSION: This is the first comprehensive analysis of CSF EV of intraspinal tumor patients. CSF EV display distinct subpopulations that may allow tumor classification and long-term surveillance. However as tumor-specific EVs may be rare, there is still the need to identify markers that can enrich tumor-specific EVs for molecular profiling.